2012
DOI: 10.1128/jcm.06036-11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Quantifying Pneumocystis jirovecii DNA by Using Real-Time PCR in Bronchoalveolar Lavage Fluid from Immunocompromised Patients

Abstract: Quantitative PCR (qPCR) is more sensitive than microscopy for detecting Pneumocystis jirovecii in bronchoalveolar lavage (BAL) fluid. We therefore developed a qPCR assay and compared the results with those of a routine immunofluorescence assay (IFA) and clinical data. The assay included automated DNA extraction, amplification of the mitochondrial large-subunit rRNA gene and an internal control, and quantification of copy numbers with the help of a plasmid clone. We studied 353 consecutive BAL fluids obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
84
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 28 publications
4
84
1
Order By: Relevance
“…Using an upper cutoff value of 1,900 trophic form equivalents/ml and a lower cutoff value of 120 trophic form equivalents/ml, this qPCR assay showed specificity and sensitivity of 100% for PCP diagnosis. Botterel et al determined P. jirovecii DNA copy numbers in BAL fluid samples using a qPCR assay also targeting the mtLSU rRNA gene (12). Using an upper cutoff value of 4 log 10 copies/l and a lower cutoff value of 2.6 log 10 copies/l, this qPCR assay showed specificity and sensitivity of 100% for PCP diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using an upper cutoff value of 1,900 trophic form equivalents/ml and a lower cutoff value of 120 trophic form equivalents/ml, this qPCR assay showed specificity and sensitivity of 100% for PCP diagnosis. Botterel et al determined P. jirovecii DNA copy numbers in BAL fluid samples using a qPCR assay also targeting the mtLSU rRNA gene (12). Using an upper cutoff value of 4 log 10 copies/l and a lower cutoff value of 2.6 log 10 copies/l, this qPCR assay showed specificity and sensitivity of 100% for PCP diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of those studies determined cutoff values for P. jirovecii DNA copy numbers in order to differentiate PCP from Pneumocystis colonization (5-12, 26). However, cutoff values differed from one study to another due to methodological differences, as various genomic targets, such as the major surface glycoprotein (MSG) gene (5,6,8,9,11), the heat shock protein 70 (HSP70) gene (7), the dihydropteroate synthase (DHPS) gene (26), and the mtLSU rRNA gene (10,12), were amplified. The mtLSU rRNA gene was used in the present study because (i) it is a multicopy gene in the P. jirovecii genome that allows highly sensitive detection, (ii) it has been routinely used for P. jirovecii detection with a plus/minus PCR assay in our laboratory for several years, and (iii) it is the target most commonly used for P. jirovecii detection worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in addition to avoiding false-positive results, qPCR offers the possibility of quantifying the fungal burden in the considered sample, and previous studies have shown that infected patients harbor higher fungal burdens than those who are only colonized (12,13). However, the interpretation of qPCR results remains challenging, since precise cutoffs to distinguish between these patients have rarely been calculated (13)(14)(15)(16)(17). Moreover, these cutoffs are difficult to compare, since either multicopy (mtLSU or MSG) or single-copy genes (DHPS or HSP70) were targeted with different technologies (FRET or TaqMan) in those studies (13,14,16,18,19).…”
mentioning
confidence: 99%
“…Clinical diagnosis of PCP is based mainly on microscopic procedures performed directly on the clinical sample and usually involves immunofluorescence microscopy (IFA) or use of Grocott's methenamine silver stain (9,10). Recently, some reports have described the utility of real-time PCR (rt-PCR) protocols to increase the sensitivity and specificity of PCP diagnosis (11)(12)(13)(14)(15)(16)(17), and some of these tests have been commercialized (18). Moreover, a recent study showed the utility of rt-PCR assays for the early diagnosis and treatment of non-HIVinfected patients diagnosed with PCP, for whom a definitive diagnosis could be performed using rt-PCR techniques that detected the low fungal burden present in the patients (19).…”
mentioning
confidence: 99%